Efficiency of germination of seeds in pre-sowing irradiation by its UV radiation of different spectral composition - Семенов, А. О.; Кожушко, Г. М.; Сахно, Т. В. (Scientific Progress & Innovations, 2018)
One of the main tasks of the agricultural complex is to increase the quantity and quality of crop production. Great interest in stimulating growth and increasing the resistance of plants to external factors and increasing the productivity of agricultural crops is the use of optical radiation – pre-sowing processing of seeds of crops by ultraviolet radiation. The effect of three different regions C (200–280 nm), B (280–320 nm) and A (320–400 nm) of ultraviolet irradiation of seeds was investigated. It is established that UV irradiation irrespective of the spectral range positively affects biological processes: germination energy, germination capacity and seed germination. The energy of germination, the capacity to germinate and the germination of seeds were determined in laboratory conditions. These indices were compared for seeds irradiated in different energy regions A, B, C of ultraviolet radiation at the same radiation dose of 120 J/m2 with control samples (without irradiation). Investigations of germination energy, germination capacity and seed germination showed that UV irradiation in different energy regions A, B, C at doses of 120 J/m2 positively affects rape seeds, as the germination energy increases by 23–31 %, the capacity to sprouting by 14–25 %, and the similarity increases by 8–17 %. In addition, studies at similar doses of UV irradiation show that the germination energy for the C region is 5–8 % higher in comparison with the UV regions A and B, while the germination capacity for the C region is greater by 9–11 %, and the similarity for region C is large by 9.2 % compared with region B, and by 6.6 in comparison with region A. Comparing the effect of the energy regions of different UV ranges on pre-sowing seed irradiation, it can be stated that UV irradiation irrespective of the spectral range positively affects the germination energy, germination capacity and seed germination.